(untitled) (Al-Aasar, 2025)
This study explores the etymology and semantic dimensions of the two Qur’anic terms: "Al-Masih" and "Ilyasin", through the lens of Arabic lexicons, Qur’anic context, and variant readings (qirāʾāt). The term "Al-Masih" is analyzed in light of its derivation—whether from masḥ (to wipe/anoint) or sayḥ (to travel)—and whether it implies an active or passive meaning. Its application to both Jesus (peace be upon him) and the Antichrist is discussed to highlight the contextual fluidity of the term within the Qur’an. The second part investigates "Ilyasin", assessing its grammatical and phonetic relationship to "Ilyas". The study reviews the opinions of linguists and exegetes, concluding that "Ilyasin" is a stylistic Qur’anic variant of "Ilyas", used for rhythmic or phonological reasons without altering the referent. Adopting a comparative linguistic approach, the paper draws from Arabic dictionaries, tafsīr works, and grammatical literature. It concludes that both terms are rich in meaning and deeply rooted in Arabic morphology and Qur’anic eloquence.